A novel VARS2 gene variant in a patient with epileptic encephalopathy - Lucija Ruzman; Ivana Kolic; Jelena Radic Nisevic; Antonija Ruzic Barsic; Ingrid Skarpa Prpic; Igor Prpic (Upsala Journal of Medical Sciences, 2019)
Background: Mitochondrial disorders are heterogeneous clinical syndromes caused by defective activity in the mitochondrial respiratory chain, resulting in a faulty oxidative phosphorylation system. These inherited disorders are individually rare, and furthermore they are phenotypic variables. The genetically characterized mitochondrial disorders are rarely associated with epileptic encephalopathies. Case presentation: We present the clinical phenotype, biochemical analysis, and electrographic and neuro-radiological features of a 5-month-old girl with epileptic encephalopathy, microcephaly, severe psychomotor delay, hypertrophic cardiomyopathy, and abnormal MRI scan. Using whole-genome sequencing technique, compound heterozygous mutations of the VARS2 gene were revealed, with one previously unreported frameshift mutation. Conclusion: Our report extends the phenotypic spectrum of VARS2-related disorders with an initial presentation of epileptic encephalopathy and early death due to malignant arrhythmia.